Sistem Pengendalian Internal Kas pada Klinik Utama Vincentius Kristus Raja Surabaya - Anita Permatasari; Jeanne Asteria Wawolangi (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2022)
The internal cash control system is important in a business unit in the form of a health clinic, because the cash element is one of the liquid current property accounts that can be used to finance the operational activities of the Main Clinic Vincentius Kristus Raja Surabaya. Research methods used by researchers in analyzing data in the form of primary data with qualitative methods. This research approach is carried out phenomenologically conducted by researchers with the aim that researchers can observe directly the reality that occurs so that they can obtain accurate information. The data collection techniques used is an interview with the head of polyclinics and clinical operations staff. Researchersvisit the clinic for observation and documentation. The results of the first study showed that the internal control system was already running in accordance with established financial procedures. The second result of the study is that the cash receipt procedure has all gone through the registration section except the dental clinic section. The third study showed that the implementing function in the operation of The Main Clinic Vincentius Kristus Raja Surabaya performs the trap of storage functions, especially in the dental health services section. The latest research results show the need for periodic monitoring or monitoring by the foundation, so that operational implementation runs smoothly and in accordance with the elements of internal control and the main clinic objectives of Vincentius Kristus Raja Surabaya can be achieved.